Microwave Assisted, One Pot Synthesis of Alkyl-3-amino-2-arylimino-1,3-thiazolan-4-ones-5-ylidene Acetate - Pourshamsian, Kh.; Montazeri, N.; Ahamadi, S.; Noghani, T. (Asian Journal of Chemistry, 2012)
Reaction of 4-phenylthiosemicarbazide and thiosemicarbazide with dialkyl acetylene dicarboxylate in CH2Cl2 at microwave irradiation lead to alkyl-3-amino-2-phenyliminothiazolidine-4-one-5-ylidene acetate and alkyl-3-amino 2-iminothiazolidine-4-one-5-ylidene acetate in moderate yields and short times. Di-t-butylacetylenedicarboxylate have a different treatment and the cyclization products is not observed. The structures of the synthesized compounds were elucidated by elemental analysis and spectral data.